Inflammatory myofibroblastic tumor of mandible: A rare case report and review of literature - Korlepara, Rajani (J Oral Maxillofac Pathol, 2017)
Inflammatory pseudotumor is a term given to different neoplastic and nonneoplastic entities that have a common histological appearance, which comprises spindle cell proliferation with a prominent chronic inflammatory cell infiltrate. Inflammatory myofibroblastic tumor (IMT) is an uncommon lesion with distinctive clinical, pathological and molecular features and is considered to be pseudotumor for the past two decades due to its appearance. IMT is an intermediate soft tissue tumor which was first observed in lungs. It was named as IMT because it mimics a malignant neoplasm clinically, radiologically and histopathologically. The most common sites are lungs, liver and gastrointestinal tract. IMT in head and neck region is exceptionally rare and the sites reported include gingiva, tongue, hard palate, mandible, buccal mucosa and submandibular salivary gland. Till now, 8 cases of intramandibular IMT were reported. Here, we report an additional case of intramandibular IMT in a 20-year-old male patient.